Kepemimpinan Visioner–Digital dan PDCA di Sekolah Swasta: PRISMA SLR dengan Validasi Lapangan (Grand Tour), 2014–2025 - Aas Amelia; Suryadi Suryadi; Moh Takdir; Syafa’at Ariful Huda (Jurnal Ilmiah Global Education, 2026)
This study aims to examine the role of visionary and digital leadership in improving the quality of private schools through a data-driven PDCA (Plan-Do-Check-Act) cycle. Using a mixed-evidence approach, this study combines a PRISMA-based Systematic Literature Review (SLR) and a grand tour to map and validate findings in the field. The results indicate that principals who implement visionary and digital leadership can foster collaboration among teachers, encourage innovation in learning, and increase transparency in performance monitoring through the use of technology such as a Learning Management System (LMS) and dashboards. Although the Plan and Do phases are effective, the Act phase of the PDCA cycle still requires strengthening documentation and more structured follow-up. This study also found that utilizing digital technology to support data-driven decision-making is crucial for achieving sustainable improvement in schools. The implication of this study is the importance of strengthening the structure of follow-up and more systematic data-driven collaboration in private schools to improve educational quality. However, this study has limitations in terms of generalizability, as it only covers one school location and does not consider other external factors.